2010
DOI: 10.1111/j.1462-2920.2010.02252.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic adaptation in Pseudomonas aeruginosa: definition of the Anr and Dnr regulons

Abstract: SummaryThe anaerobic metabolism of the opportunistic pathogen Pseudomonas aeruginosa is important for growth and biofilm formation during persistent infections. The two Fnr-type transcription factors Anr and Dnr regulate different parts of the underlying network in response to oxygen tension and NO. Little is known about all members of the Anr and Dnr regulons and the mediated immediate response to oxygen depletion. Comprehensive transcriptome and bioinformatics analyses in combination with a limited proteome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
209
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(225 citation statements)
references
References 105 publications
(131 reference statements)
12
209
0
4
Order By: Relevance
“…However, the important question of whether oxygen availability influences the T3SS in P. aeruginosa remains to be addressed. While transcriptome analyses of the molecular response of P. aeruginosa to low oxygen have not yet identified any alteration in T3SS-associated gene expression (AlvarezOrtega & Harwood, 2007;Trunk et al, 2010), T3SS-associated gene expression is induced in anaerobic biofilms (Waite & Curtis, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the important question of whether oxygen availability influences the T3SS in P. aeruginosa remains to be addressed. While transcriptome analyses of the molecular response of P. aeruginosa to low oxygen have not yet identified any alteration in T3SS-associated gene expression (AlvarezOrtega & Harwood, 2007;Trunk et al, 2010), T3SS-associated gene expression is induced in anaerobic biofilms (Waite & Curtis, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, CF-associated pathogens may only survive and persist in the infected lung by adapting to limiting oxygen stress. P. aeruginosa perceives and responds to low oxygen stress via the global anaerobic stress response regulator Anr (Sawers, 1991;Trunk et al, 2010;Zimmermann et al, 1991). Anr is a homologue of the Escherichia coli anaerobic response master regulator FNR, and it functions by regulating a large number of genes required for anaerobic respiration, including dnr and the narXL two-component system (Sawers, 1991;Trunk et al, 2010;Zimmermann et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sequence identical to that recognized by the oxygensensitive transcriptional regulator Anr is present within the plcH promoter region (Galimand et al, 1991;Trunk et al, 2010). Anr mainly acts as a regulator of gene expression under micro-oxic and anoxic conditions (Arai et al, 1995;Kawakami et al, 2010;Lu et al, 1999;Ye et al, 1995), and its activity increases as oxygen tensions decrease.…”
Section: Oxygen Limitation Represses Plch Activity In P Aeruginosamentioning
confidence: 99%
“…The histone-like nucleoid-associated proteins MvaT and MvaU were both shown to bind and inhibit the transcription of the plcH ORF in P. aeruginosa (Castang et al, 2008). Several publications have reported that a canonical Anr consensus sequence is positioned within the plcH promoter (Galimand et al, 1991;Trunk et al, 2010), suggesting a role for negative regulation of plcH by Anr. However, this regulatory scheme has not been established.…”
Section: Introductionmentioning
confidence: 99%